Coping strategies: Seeking personalized care in relapsing-remitting multiple sclerosis. A patient reported measure–coping responses inventory. Issue 1 (February 2021) - Vanotti, Sandra; Cabral, Nadia; Eizaguirre, Maria Barbara; Marinangeli, Aldana; Roman, Maria Sol; Alonso, Ricardo; Silva, Berenice; Garcea, Orlando
Background: Coping is defined as a set of cognitive and behavioral efforts made to master stressful specific demands. Adaptation to chronic diseases, such as Multiple Sclerosis (MS), depends on the effectiveness of coping. Objective: To assess the psychometric properties of the Coping Responses Inventory (CRI-A) in persons with MS (PwMS), verifying the transferability of the measure, already validated in the Argentine general population, and to describe the types of coping strategies available for PwMS. Methods: 90 PwMS were included. Outcome measures: CRI-A Inventory, Expanded Disability Status Scale (EDSS), Beck Depression Inventory, Fatigue Severity Scale and MS International Quality of Life questionnaire. Results: Descriptive data is as follows: mean age (years): 40.97 ± 12.85; years of education: 13.46 ± 3.93; EDSS: 2.48 ± 1.79; disease evolution (years): 10.76 ± 9.72; depression: 13.92 ± 10.45; fatigue 3.77 ± 1.72. The psychometric properties of the CRI-A Inventory observed in the Argentine general population are present in the MS sample as well, with adequate validity and reliability. The respondents most frequently utilized a problem-focused coping style. Conclusions: Results showed the CRI-A has good transferability properties from the Argentine general population to the MS population.